Work-Family Conflict and Social Support: A Study of Women Academics in Java Indonesia - Nurhidayati (Curtin University, 2014)
This thesis was designed to examine the experience of work-family conflict and social support mechanisms used to manage work-family conflict by married women academics with children in Java, Indonesia. A mixed methods study using three stages was designed to address the research questions. Cultural factors are considered to be critical factors in understanding work-family conflict and are used to describe the social support mechanisms used by female academics in Java Indonesia.